Setting the agenda: Climate change adaptation and mitigation for food systems in the developing world - Wollenberg, Eva Karoline; Herrero, Mario; Wassmann, Reiner; Neufeldt, Henry; Vermeulen, Sonja J.; Rosswall, T.; Campbell, Bruce M.; Hellin, Jonathan; Jarvis, Andy; Challinor, Andrew J.; Snook, Laura K.; Smakhtin, Vladimir U.; et al. (2012)
New agricultural development pathways are required to meet climate change adaptation and mitigation needs in the food systems of low-income countries. A research and policy agenda is provided to indicate where innovation and new knowledge are needed. Adaptation requires identifying suitable crop varieties and livestock breeds, as well as building resilient farming and natural resources systems, institutions for famine and crop failure relief, and mechanisms for rapid learning by farmers. Mitigation requires transitioning to ‘low climate impact’ agriculture that reduces emissions while achieving food security, economic well-being and sustainability. Efficient interventions, incentives for large-scale shifts in practices, and monitoring systems are required. Integrated assessments of adaptation and mitigation are needed to better understand the synergies and trade-offs among outcomes.